A Critical View on Brevity - Mostafa Sharifi Abnavi; Zahra Rahimi (مطالعات زبانی و بلاغی)
As one of the major topics in the science of rhetorical meaning, brevity has long been a focal point of scholarly inquiry. In the earliest rhetorical texts, brevity was divided into two main types of elliptical and concise brevity. However, the lack of a comprehensive framework and precise definitions for these two types has made it impossible to confidently place all concise phrases or sentences into one of these categories. Therefore, the present research aims to redefine this concept and propose a new classification of brevity. This research has been conducted using a descriptive-analytical method, based on extensive library and documentary studies, and attempts to provide a comprehensive and solid definition as well as an accurate criterion for identifying different types of brevity. The findings of this study suggests that brevity can be examined from two main perspectives. The artistic or rhetorical perspective relates to its impact and aesthetic functions in the text, and the structural perspective refers to the way the concise phrase is organized. From the structural perspective, brevity is divided into two general types of elliptical and concise. Elliptical brevity is further divided into two main branches; elliptical brevity through verbal cues explains the omission of part of a phrase based on the presence of verbal evidence, and elliptical brevity through contextual cues occurs by relying on implicit and meaning-based understanding. Likewise, concise brevity is divided into two types; concise brevity in expression is achieved through rhetorical devices, and non-expressive concise brevity focuses on direct and simple structures. While addressing the gaps in previous studies, this new classification offers a more accurate analysis and comprehensive categorization of brevity and provides a practical tool for researchers in the field of rhetoric.